Impurity ion heating and drift velocity in the AL'FA experiment - McNeill, D.H. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
High impurity ion energies (>100 eV) and toroidal drift velocities were reported in the early, ohmically heated experiment, Al'fa (Альфа, ~1960, major radius 1.6 m). These are explained here in terms of charged particle acceleration by the toroidal electric field corresponding to the noisy loop voltage, using data from the experiment, atomic cross section data, and 1-D momentum equations without turbulence, radial fluxes, or microfield anomalies. In general, the impurities are thermally decoupled from the H (bulk) ions and electrons in the transiently runaway discharges.